2009
DOI: 10.1182/blood.v114.22.920.920
|View full text |Cite
|
Sign up to set email alerts
|

Final Results of a Phase II Trial of Belinostat (PXD101) in Patients with Recurrent or Refractory Peripheral or Cutaneous T-Cell Lymphoma.

Abstract: 920 Background: Belinostat is a pan-HDAC inhibitor of the hydroxamate chemical class that is well-tolerated and has shown clinical activity. Methods: Open label, multicenter trial enrolling patients (pts) with peripheral T-cell lymphoma (PTCL) or cutaneous T-cell lymphoma (CTCL) who failed ≥ 1 prior systemic therapy. Pts received 1000 mg/m2 IV belinostat over 30 min on days 1 to 5 of a 3-wk c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Thus the disruption of multiple pathways by HDAC inhibitors and their lack of enzyme specificity cause additional complication to rational drug design for a specific disease state. In clinical studies several classes of HDAC inhibitors demonstrated potent anticancer activities with remarkable tumor specificity, such as cutaneous T-cell lymphoma and peripheral T-cell lymphoma [ 26 , 27 , 28 , 29 ].…”
Section: Histone Deacetylases and Cancermentioning
confidence: 99%
“…Thus the disruption of multiple pathways by HDAC inhibitors and their lack of enzyme specificity cause additional complication to rational drug design for a specific disease state. In clinical studies several classes of HDAC inhibitors demonstrated potent anticancer activities with remarkable tumor specificity, such as cutaneous T-cell lymphoma and peripheral T-cell lymphoma [ 26 , 27 , 28 , 29 ].…”
Section: Histone Deacetylases and Cancermentioning
confidence: 99%
“…Other hydroxamic acids or cinnamic hydroxamic acids derivatives currently in clinical trials are belinostat (PXD101), panobinostat (LBH589) and givinostat (ITF2375). Belinostat has been reported to have a good safety profile and patients showed clinical response both during preclinical trials and a phase II trial (Plumb et al., 2003; Pohlman et al., 2009). Additionally, the pan‐HDAC inhibitor givinostat showed some promising results for haematological malignancies, e.g.…”
Section: Clinical Applicationmentioning
confidence: 99%
“…Additional HDAC inhibitors, including potent pan‐HDAC inhibitors, appear to have activity in CTCL . Further studies are needed to fully define the mechanisms of resistance to HDAC inhibition in CTCL , enabling the development of rational therapeutic combinations incorporating HDAC inhibitors in CTCL .…”
Section: Treatment Of Advanced‐stage Mf/ssmentioning
confidence: 99%